Inhibiting and Supporting Factors of Land Administration Interoperability from a Governance Networks Perspective - Ramones Ramones; Susanti Susanti; Tora Akadira (Sean Institute, 2026)
Digitizing land services through electronic land certificates is part of the digital public administration agenda in Indonesia. However, its implementation still faces serious challenges related to system interoperability between agencies. This study aims to analyze strategies for developing electronic land certificate interoperability in land administration in Indonesia. The study used a qualitative approach with an exploratory design through semi-structured interviews, policy document studies, and thematic analysis. The results indicate that interoperability is suboptimal due to system fragmentation, regulatory disharmony, and limited cross-agency coordination. This study emphasizes that interoperability is not merely a technical issue but also an issue of digital public administration governance. This research contributes to the development of a strategic framework for land administration interoperability that focuses on legal certainty and effective public services.